Effect of heat treatment on properties and microstructure of steels. (2021) - Chandra Kandpal, Bhaskar; Gupta, D.K.; Kumar, Ashok; Kumar Jaisal, Ashish; Kumar Ranjan, Atul; Srivastava, Ankit; Chaudhary, Prashant
Abstract: In this study EN 31, EN 24 and EN 8 (alloy steel) are selected as specimens for testing various mechanical properties and microstructure change. The effects of heat treatment on the mechanical properties and microstructure characteristics change of selected specimen are analyzed. Annealing, normalizing and hardening are the most important heat treatment processes often used to change mechanical properties of engineering materials. The purpose of heat treating is to analyze the mechanical properties of the steel, usually ductility, hardness, Yield strength, tensile strength and impact resistance. The heat treatment develops hardness, softness, and improves the mechanical properties such as tensile strength, yield strength, ductility, corrosion resistance and creep rupture. These processes also help to improve machining effect, and make them versatile. The mechanical properties can easily be modified by heat treating to suit a particular design purpose. In the present study, selected samples are heat-treated at certain temperature above the austenitic region and quenched in order to investigate the effect on the mechanical properties and microstructure of the steel. The changes in mechanical behavior and microstructure as compared with unquenched samples are explained in terms of changes in tensile strength. Results showed that the mechanical properties of mild steel can be changed and improved by various heat treatments for a particular application. It was also found that the annealed samples with mainly ferrite structure gave the lowest tensile strength and hardness value and highest ductility and toughness value while hardened sample which comprise martensite gave the highest tensile strength and hardness value and lowest ductility and toughness value.